Integrated landscape approach: closing the gap between theory and application - Bürgi, Matthias; Ali, Panna; Chowdhury, Afroza; Heinimann, Andreas; Hett, Cornelia; Kienast, Felix; Mondal, Manoranjan Kumar; Upreti, Bishnu Raj; Verburg, Peter H. (MDPI, 2017)
Recently, the integrated landscape approach has gained increasing interest of the scientific community, as well as of organizations active in the field of sustainable development. However, the enthusiastic welcome is challenged by little consensus on theory, terminology and definitions. Moreover, the operationalization of the approach into practice is a major challenge. In this paper, we present a framework to operationalize the integrated landscape approach in practice by putting a long-term collaboration between scientists and various stakeholder at center stage. Based on encompassing understanding of landscape-level processes and interactions, four pillars addressing different steps of a joint-learning circle are described and illustrated with examples. We consider the integrated landscape approach to be a prime way of targeting the Sustainable Development Goals (SDGs), but novel forms of collaboration between scientists and other stakeholders based on long-term commitments will be needed for operationalization in practice.